How Social Infrastructures of Care and Solidarity Cope with the COVID-19 Pandemic: A Reflection from Community Networks of the Baan Mankong Programme in Thailand. (May 2022) - Wungpatcharapon, Supreeya; Pérez-Castro, Brenda
Low-income citizens in urban areas have been highly vulnerable to the COVID-19 outbreak around the world. The pandemic has revealed and deepened the unequal distribution of resources, as well as the inability of national, state and local governments to respond to such crises. In Thailand, the Community Organizations Development Institute (CODI) supported the community networks associated with their collective housing credit programme, Baan Mankong. CODI not only put a 3-month moratorium on Baan Mankong, but also released an urgent COVID-19 relief fund of 4.5 million, for communities under the same programme, nationwide. There were 228 initiatives proposed by the urban poor networks, which received approximately 2.2 million, implemented between April and September 2020. Community kitchens, community-run shops, community gardens, income-generation activities, and online and offline community markets are among the activities—along with diverse mechanisms to manage them collectively—devised by the community groups to respond to the socioeconomic impacts of the pandemic. Drawing on information from online surveys, focus group discussions and case studies, this article highlights the mechanisms used and outcomes achieved by these community initiatives. More importantly, the article points at how the underlying social infrastructures of care and solidarity embedded in the community networks actively participating in Baan Mankong were crucial to cope with COVID-19 and constitute the basis for long-term rehabilitation and further development of low-income communities in Thailand.